Complete Hydrogen Production from Hydrazine Borane over Raney Ni Catalyst at Room Temperature. Issue 3 (6th March 2019) - Zhang, Shiliang; Yao, Qilu; Li, Qingyang; Feng, Gang; Lu, Zhang-Hui
Abstract : The synthesis of noble‐metal‐free recyclable catalysts with prominent catalytic performance for the complete hydrogen production from hydrazine borane (N2 H4 BH3, HB) is of great significance in achieving a hydrogen economy‐based society. Herein, Raney Ni is synthesized using a rapidly quenched aluminum–nickel alloy under a typical alkali leaching condition and is used to catalytically convert hydrogen of N2 H4 BH3 to H2 via hydrolyzing BH3 groups and decomposing the N2 H4 moiety in alkaline conditions. It is the first report of a noble‐metal‐free catalyst achieving a complete production of hydrogen from N2 H4 BH3 at room temperature. This noble‐metal‐free catalyst might tremendously broaden the actual utilization of HB as a promising chemical hydrogen storage material. In addition, such a simple strategy can also be expanded to design and synthesize other porous metals for more applications. Abstract : Raney Ni is facilely synthesized and used as a noble‐metal‐free recyclable catalyst for hydrogen production from N2 H4 BH3 . The complete conversion of hydrogen of N2 H4 BH3 to H2 can be achieved by Raney Ni at room temperature, with a turnover frequency value of 892 h −1 . Raney Ni also exhibits perfect magnetic properties and can be easily collected and reused.